Omnibus Law and the Challenges of the Indonesian Agricultural Sector: an Islamic Perspective - Rasyid, Tengku Harunur; Kusumawaty, Yeni (Islamic Research, 2022)
In late 2020, the Indonesian Parliament enacted the Job Creation Law, known as the "Omnibus Law," which introduced significant amendments to various sectors, including agriculture. The law aims to boost food trade and increase private sector involvement in enhancing agricultural productivity. However, critics argue that the law disadvantages farmers by deprioritizing local agricultural products and heavily relying on imports to meet domestic food supply needs. Additionally, the law removes restrictions on foreign investment in horticulture and establishes a land bank to manage and redistribute idle lands. This article aims to analyze the impact of the Omnibus Law on Indonesia's agricultural sector, assessing its implications through both descriptive analysis and an Islamic perspective. A descriptive analysis approach was employed to compare the Omnibus Law with previous agricultural laws. The study evaluates the substance of the law, its effects on the agricultural sector, and its alignment with Islamic principles. The analysis reveals significant changes in agricultural policies, including increased reliance on imports, reduced prioritization of local products, and expanded foreign investment opportunities. These shifts present challenges for farmers and raise concerns about the sustainability of Indonesia's agricultural sector. By incorporating an Islamic perspective, this study highlights the need for a balanced approach that ensures fairness for farmers while supporting national agricultural productivity. The findings suggest policy adjustments to better align the Omnibus Law with sustainable and inclusive agricultural development in Indonesia.